2016
DOI: 10.17221/8783-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent effective population size mating as a useful tool in the genetic management of the Ibicenco rabbit breed (Conill Pages d'Eivissa)

Abstract: ABSTRACT:The Ibicenco rabbit (Conill Pages D'Eivissa) is a rare breed mainly located on Ibiza Island, in rural areas. Today breeders are looking for a sustainable use and alternative routes for profitability of the population to avoid its extinction. The breed presents some variety in coat colour (brown, black, orange, and grey), and breeders would like to maintain these characteristics. The objectives of this study were to develop a method to design matings in a population with unbalanced pedigree depth in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Nagy et al (2010) studied the generation interval on Pannon White rabbits in Hungary and reported the overall mean as 1.211 yr for the whole population. Similar study was carried out on Sika rabbits in Slovenia by Planinc et al (2012) and Ibicenco rabbits in Spain by Martín de la Rosa et al, (2016) who reported the mean generation intervals as 1.16 and 1.0 yr, respectively.…”
Section: Generation Intervalsupporting
confidence: 77%
See 3 more Smart Citations
“…Nagy et al (2010) studied the generation interval on Pannon White rabbits in Hungary and reported the overall mean as 1.211 yr for the whole population. Similar study was carried out on Sika rabbits in Slovenia by Planinc et al (2012) and Ibicenco rabbits in Spain by Martín de la Rosa et al, (2016) who reported the mean generation intervals as 1.16 and 1.0 yr, respectively.…”
Section: Generation Intervalsupporting
confidence: 77%
“…The knowledge on pedigree completeness is important, as the inferences drawn on inbreeding and effective population size depend on it. The pedigree depth is important because it plays a significant part in the rest of the parameters that require genealogical data for their calculation (Martín de la Rosa et al, 2016). Up to 5 th generation, 71.29% pedigree was complete (Figure 1).…”
Section: Pedigree Completenessmentioning
confidence: 99%
See 2 more Smart Citations
“…The effective population size (Ne) was estimated based on two approaches (NeI and Nec) implemented in Endog version 4.8 60 . First, Ne was calculated to estimate the founder population size and to detect the existence of bottlenecks and possible consequences of the mating strategy, via the individual increase in inbreeding (NeI), as proposed by De la Rosa et al 67 . To calculate NeI, the coefficient of individual increases in inbreeding (∆Fi), determined according to Falconer and Mackay 68 and modified by Gonzales-Recio et al 69 and Gutiérrez et al 70 , was used.…”
Section: Studbook Data and Pedigree Analysesmentioning
confidence: 99%